Tindak Pidana Korupsi Perspektif Hukum Pidana Indonesia dan Fiqih Jinayah - Muttaqin, Ichwan; Al Djufri, Helmi (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
The Corruption Crime is a crime that harms society and the state. In the perspective of Indonesian criminal law, corruption is regulated in Law No. 31 of 1999 concerning the Eradication of Corruption Crime. Meanwhile, in the perspective of fiqh jinayah, corruption can be categorized as a jarimah that violates the rights of Allah and human rights. This study aims to analyze corruption crime in the perspective of Indonesian criminal law and fiqh jinayah, as well as a comparison between the two. This study uses library research methods with a normative and comparative juridical approach. The results show that both Indonesian criminal law and fiqh jinayah have the goal of creating justice and protecting society from crime. However, there are differences in the approach and sanctions applied. This research is expected to contribute to the understanding of corruption crime and efforts to eradicate it.